EFFICACY OF MESENCHYMAL STEM CELLS USED FOR THE IMPROVEMENT CEREBRAL MICROCIRCULATION IN SPONTANEOUSLY HYPERTENSIVE RATS - Sokolova, I B; Polyntsev, D G (T͡S︡itologii͡a, 2017)
Elaboration of new methods of correction of microcirculatory disorder in the brain caused by persistent high blood pressure is a topical task both for medicine and for biology. We studied influence of intracerebral transplantation of human mesenchymal stem cells (MSCh) to cerebral microcirculation in young (4 months) and aged (12 months) spontaneously hypertensive rats (SHR). It was shown that transplantation MSCh promoted the rise of the density of microvascular network of young SHR ca. 1.6-fold; density of the arteriolar area of microvascular network of the pia mater increased ca. 1.9-fold. The density of microvascular network of aged SHR increased ca. 1.4—1.5-fold after transplantation MSCh. The perfusion and tissue saturation of sensorimotor cortex of young SHR increased to the level of young normotensive rats, and in aged SHR the perfusion and tissue saturation of sensorimotor cortex was not increased. Conclusion: the intracerebral transplantation MSCh almost completely leveled the pathological changes of the microcirculation in the sensorimotor cortex of the brain of young SHR and improved unimportantly microcirculation in aged SHR.